Holistic Approaches in the Management of Alcohol Use Disorder: A Systematic Review of Ayurvedic Interventions - Prof. Anita Sharma; Prof. Sanjeev Sharma; Dr. Amol Sudhakar Kadu; Dr. Dinesh Kumar Kumawat; Dr. Mukesh Kumar Saini (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Alcohol Use Disorder (AUD) is a chronic condition marked by a compulsive desire for alcohol, loss of control, and significant physical and psychological dependency. Conventional treatments for AUD often come with side effects, relapse, and incomplete recovery. Ayurveda, with its holistic approach, offers potential in addressing both the physiological and psychological dimensions of AUD. This review explores Ayurvedic interventions, including detoxification, herbal formulations, and psychological approaches, for managing AUD. Methods: A systematic review was conducted following the PRISMA guidelines, including studies published between 2010 and 2024. The search was carried out on databases like PubMed, AYUSH Research Portal, and Google Scholar. Eligible studies included randomized controlled trials (RCTs), non-randomized clinical trials, case reports, and observational studies that evaluated Ayurvedic therapies for AUD. Key outcomes included reduction in alcohol consumption, withdrawal symptoms, oxidative stress markers, and improvements in psychological health. Results: Fourteen studies fulfilling the inclusion criteria were included in the review. Most studies investigated the effects of Panchakarma therapies (e.g., Virechana, Basti, Nasya), herbal formulations (e.g., Arogyavardhini Vati, Ashtang Lavan Churna), and Satvavajay Chikitsa (psychological counseling). Results indicated significant improvements in withdrawal symptoms, reduced alcohol cravings, and improved liver function. Panchakarma therapies showed efficacy in detoxification and managing oxidative stress markers, while herbal treatments and psychological interventions demonstrated promising effects on reducing relapse rates and improving emotional stability. Discussion: The findings suggest that Ayurvedic interventions offer a comprehensive treatment strategy for AUD, addressing both the physical and psychological aspects of addiction. The combination of detoxification, herbal support, and psychological counseling aligns with the holistic nature of Ayurvedic medicine and offers potential advantages over conventional treatments. However, further high-quality clinical trials are needed to standardize these interventions and establish robust evidence for their clinical application. Conclusion: Ayurvedic therapies, particularly Panchakarma, herbal formulations, and psychological interventions, show promising potential in the management of AUD. The holistic nature of Ayurveda offers a complementary approach to conventional treatments, emphasizing detoxification, emotional well-being, and long-term recovery. Further research with standardized protocols is necessary to validate and optimize these interventions in clinical settings.